2011
DOI: 10.5005/jp-journals-10019-1027
|View full text |Cite
|
Sign up to set email alerts
|

A Comparative Study on the Effect of Two Different Investing Mediums on the Movement of Artificial Teeth during the Fabrication of Complete Denture: An in vitro Study

Abstract: Acrylic processing of waxed-up dentures is considered to be a crucial and technique-sensitive procedure. Even after investing a lot of time and clinical skill a definitive movement of teeth during and after processing has long been observed which lead to occlusal discrepancies and disturb the harmonious occlusal scheme achieved earlier. Shifting of the teeth can occur as a result of the investing procedures and investing materials. The objective of this study was to evaluate and compare the movement of artific… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 21 publications
0
1
0
Order By: Relevance
“…Studies found that there is still no certain technique whether a conventional or CAD/CAM that can entirely eliminate denture teeth movement. (9,10) Materials and methods -This in-vitro study was applied on an educational maxillary edentulous model made of dental stone.…”
Section: Introductionmentioning
confidence: 99%
“…Studies found that there is still no certain technique whether a conventional or CAD/CAM that can entirely eliminate denture teeth movement. (9,10) Materials and methods -This in-vitro study was applied on an educational maxillary edentulous model made of dental stone.…”
Section: Introductionmentioning
confidence: 99%